Influencing Factors and Improvement Strategies of College Students’ Participation in Voluntary Services from the Perspective of MOA - Xu, Wuyuanyuan (Journal of Educational Research and Policies, 2026)
To improve the voluntary service system in the new era, enhance the effectiveness of talent cultivation in colleges and universities, and address the practical dilemmas in college students’ participation in voluntary services, this study, based on the MOA theoretical framework (Motivation-Opportunity-Ability) and using the fsQCA method, analyzes the key influencing factors and their mechanism of action on college students’ participation in voluntary services from a configurational perspective, with 351 valid questionnaires as samples. The results show that college students’ participation in voluntary services is the result of the non-linear synergy of three-dimensional factors: motivation (public welfare spirit, self-growth), opportunity (campus atmosphere, organizational management), and ability (voluntary skills, self-efficacy). These factors can be summarized into three models: campus atmosphere-driven model, self-ability growth-driven model, and public welfare spirit-led model. Based on this, the study proposes strategies from three aspects—improving university governance, strengthening organizational capacity, and optimizing policy support—to provide references for promoting the high-quality development of college students’ voluntary services.